Health Literacy with COVID - 19 Prevention Behavior among Informal Workers in The Post-pandemic Situation in Chumphon Province - Chutipattana, Nirachon; haohan, nisarat (Princess of Naradhiwas University Journal, 2025)
This cross -sectional study aimed to examine the relationship between health literacy and prevention behaviors of COVID-19 among informal workers during the post pandemic period in Chumphon province. Data were collected from 427 samples by using multistage sampling. Instruments used in this study were closed-ended questionnaire that created by the researcher were validated content by five experts, including health care professionals, experts in health education and behavioral science, experts in epidemic control and prevention, and experts in health literacy. The content validity was good at 0.93. The content validity was high at 0.93, and the reliability index was tested using tools that were deemed suitable by experts to test with informal workers who shared characteristics with the samples. The reliability index was high at 0.92, the literacy portion equaled 0.89, and the behavior component equaled 0.90. Data were analyzed by using descriptive statistics including frequency, percentage, average, standard deviation, and Pearson’s Correlation Coefficient. Results found that informal workers had health literacy in a moderate level ( = 121.91,S.D. = 18.69) and prevention behaviors of COVID-19 was also in a moderate level ( = 80.29,S.D. = 13.63). There was a statistically significant relationship between the healthcare facilities accessed and health literacy (P<0.05). The findings of this study can be applied to the design of behavioral modification strategies and the monitoring and prevention of emerging diseases among the working-age population in the future.